Cardiac arrhythmias misdiagnosed as epilepsy. Issue 1 (January 1985) - Rutter, N; Southall, D P
Abstract : A mother and three children presenting with syncope induced by exercise and emotion were diagnosed as epileptic. They, and three symptom free children, showed frequent ventricular and supraventricular tachyarrhythmias on ambulatory electrocardiographic monitoring. Three died before the correct diagnosis of disordered sympathetic innervation of the heart was made, but episodes of syncope and cardiac arrhythmias in the survivors have been successfully treated by propranolol.